Influence of Wind-Driven Rain on the Thermal Conductivity of Building Envelopes with Different Cement-Lime Coatings - Juras, Peter; Durica, Pavol (Communications - Scientific letters of the University of Zilina, 2014)
This paper deals with influence of the wind-driven rain on the building envelopes in terms of thermal conductivity. Low rise building was simulated in Computational fluid dynamics CFD software OpenFOAM using Eulerian multiphase model for rain phase and determined rain load was used as an input for Heat-Air-Moisture HAM simulation in WUFI. Two different wall constructions which were used differ in the core layer and also in exterior coatings. The influence of wind-driven rain load on the thermal conductivity for aerated concrete and aerated clay brick was established.